EFFECT OF SELECTED YOGASANAS ON DIABETES AMONG ENGINEERING COLLEGE WOMEN FACULTY OF HYDERABAD (International Journal of Food and Nutritional Sciences, 2021)
The purpose of this study is to analyze the effect of Yogasanas on diabetes of engineering college women faculty. Hence 40 subjects were randomly selected whose age range between 35 to 50 years and based on their mean random blood sugar level grouped into two, control group and experimental group. Pre tests were conducted for all the subjects on selected physiological and biochemical variables such as systolic blood pressure, diastolic blood pressure, postprandial blood glucose and fasting blood sugar. The experimental group underwent yogasanas for twelve weeks. After the experimental period, the post tests were conducted on the same dependent variables. The difference between initial and final scores was considered as the effect of respective treatment. To test statistical significance, ANCOVA was used. In all cases 0.05 level was fixed to test the hypothesis of this study.